Internalisasi Nilai-nilai Pendidikan Agama Islam dalam Meningkatkan Religius Culture di SMA Negeri 3 Putra Bangsa Lhoksukon - Anisah, Nur (Pascasarjana IAIN Lhokseumawe, 2022)
This study aims to describe and explore patterns of internalization of Islamic Religious Education (PAI) values in improving religious culture at State Senior High School (SMA Negeri 3) Putra Bangsa, Lhoksukon, North Aceh through planning, implementation, and evaluation. The approach taken is a descriptive qualitative approach. Data were analyzed by using the stages of data collection, data reduction, data presentation, and drawing conclusions/data verification. The results of the research are: 1) planning for the internalization of PAI values in improving the quality of religious culture is carried out by deliberation and consensus activities which are attended by school principals, committees, deputy principals, and teachers. 2) The implementation of internalization of PAI values to improve the quality of religious culture, is carried out in several steps: (a) the principal gives authority to teachers in carrying out extracurricular activities and intracurricular activities, (b) religious activities are always inserted in each subject and supervised, (c) the methods used in internalizing PAI values to exemplary and habituating students, (d) the teacher also provides guidance to students in carrying out extracurricular activities and extracurricular activities and provides rewards to students who excel in these religious activities, (e) the school principal gives reprimands and advice to students who do not carry out religious activity programs in good language. 3) Evaluation of the internalization of the values of Islamic religious education in improving the quality of religious culture is carried out at the end of each learning semester. The evaluation in question is an evaluation of teacher performance and evaluation of religious activities carried out at school.